2010
DOI: 10.1111/j.1471-0528.2010.02714.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin to augment labour during home births: an exploratory study in the urban slums of Dhaka, Bangladesh

Abstract: Objective In Bangladesh, the majority of women give birth at home. There is anecdotal evidence that unqualified allopathic practitioners (UAPs) administer oxytocin at home births to augment labour pain. The objective is to explore the use of oxytocin to augment labour pain during home births in an urban slum in Dhaka, Bangladesh.Design Cross-sectional survey.Setting KamrangirChar slum, Dhaka, Bangladesh.Population Married women with a home birth or who experienced labour at home in the 6 months prior to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…Many respondents within these cadres described the need to increase pain in order to facilitate delivery, generally achieved through oxytocin injections. Several respondents described women needing caesarean sections because the “pain didn’t come.” This is similar to findings by other researchers in India and South Asia [17], [18]. Given that mothers-in-law frequently described believing that women today could not sustain or handle labor and delivery pain, it is possible that delivering women feel pressure to demonstrate “appropriate” childbirth by taking injections that increase labor pains.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Many respondents within these cadres described the need to increase pain in order to facilitate delivery, generally achieved through oxytocin injections. Several respondents described women needing caesarean sections because the “pain didn’t come.” This is similar to findings by other researchers in India and South Asia [17], [18]. Given that mothers-in-law frequently described believing that women today could not sustain or handle labor and delivery pain, it is possible that delivering women feel pressure to demonstrate “appropriate” childbirth by taking injections that increase labor pains.…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies have documented inappropriate use of uterotonics in South Asia, particularly in India and Bangladesh [10], [16], [17]. Intramuscular (IM) oxytocin injection during the first and second stages of labor can be dangerous because dosing cannot be adjusted in response to the strength of uterine contractions, increasing risks of uterine rupture and harm to the fetus [13].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Nguefack et al reported that 71% of cases with uterine rupture used misoprostol [9]. Studies in Bangladesh and India report the use of oxytocin by unqualified allopathic practitioners (UAP) providing health services to the poor [15]. These providers are close to homes, willing to make house calls, trusted by the community, have longer working hours and offer services at lower costs.…”
Section: Use Of Oxytocin and Prostaglandinsmentioning
confidence: 99%
“…UAPs, comprising village doctors (VDs) and unlicensed drug sellers, have limited training of a few weeks to a few months from semiformal private institutions, focused on common illnesses and diseases, and rarely on labour or delivery. These training institutions are unregulated and do not follow a standard [15]. This type of practice should be discouraged because it is associated with obstetric and neonatal complications such as uterine rupture [15].…”
Section: Use Of Oxytocin and Prostaglandinsmentioning
confidence: 99%
See 1 more Smart Citation